Cost-effectiveness of artemisinin-naphthoquine versus artemether-lumefantrine for the treatment of uncomplicated malaria in Papua New Guinean children - Moore, Brioni; Davis, W.; Clarke, P.; Robinson, L.; Laman, M.; Davis, T. (BioMed Central, 2017)
© 2017 The Author(s). Background: A recent randomized trial showed that artemisinin-naphthoquine (AN) was non-inferior to art emether-lumefantrine (AL) for falciparum malaria and superior for vivax malaria in young Papua New Guinean children. The aim of this study was to compare the cost-effectiveness of these two regimens. Methods: An incremental cost-effectiveness analysis was performed using data from 231 children with Plasmodium falciparum and/or Plasmodium vivax infections in an open-label, randomized, parallel-group trial. Recruited children were randomized 1:1 to receive once daily AN for 3 days with water or twice daily AL for 3 days given with fat. World Health Organisation (WHO) definitions were used to determine clinical/parasitological outcomes. The cost of transport between the home and clinic, plus direct health-care costs, served as a basis for determining each regimen's incremental cost per incremental treatment success relative to AL by Day 42 and its cost per life year saved. Results: In the usual care setting, AN was more effective for the treatment of uncomplicated malaria in children aged 0.5-5.9 years. AL and AN were equally efficacious for the treatment of falciparum malaria, however AN had increased anti-malarial treatment costs per patient of $10.46, compared with AL. AN was the most effective regimen for treatment of vivax malaria, but had increased treatment costs of $14.83 per treatment success compared with AL. Conclusions: Whilst AN has superior overall efficacy for the treatment of uncomplicated malaria in PNG children, AL was the less costly regimen. An indicative extrapolation estimated the cost per life year saved by using AN instead of AL to treat uncomplicated malaria to be $12,165 for girls and $12,469 for boys (discounted), which means AN may not be cost-effective and affordable for PNG at current cost. However, AN may become acceptable should it become WHO prequalified and/or should donated/subsidized drug supply become available.